THE STUDY OF EMOTIONAL BURNOUT IN CONNECTION WITH LIFE MEANING AND CAREER ORIENTATIONS AMONG REPRESENTATIVES OF SOCIONOMIC PROFESSIONS - E. Yu. Cherniakevich; E. V. Pogodina (Вестник университета, 2020)
The study results of life meaning, career orientations and emotional burnout syndrome among representatives of socionomic (helping) professions have been described. The purpose of the work was to identify the characteristics of emotional burnout, career and life meaning orientations of the personality and their relationships. To achieve the goal of the study, V. V. Boyko’s “Method for diagnosing the level of emotional burnout”, D. A. Leontiev’s test of “Life Sense Orientations” (LSO), and E. Shein’s “Career Anchors test” have been used. It has been established, that the “Resistance” phase is in the formation stage, the “Stress” and “Depletion” phases were not formed. The leading career orientation of specialists is “professional competence”. As a result of the study, the interrelation of indicators of emotional burnout, career and life meaning orientations, has been identified. High scores on the scales of the LSO: “goals in life”, “life process”, “locus of control – life”, “locus of control – I” have been found. It has been established that career-oriented industrial professionals are more susceptible to emotional burnout. The article is a contribution to the study of various aspects of helping a person experiencing emotional burnout syndrome.